Prevalence and genomic characterization of Salmonella isolates from commercial chicken eggs retailed in traditional markets in Ghana - Archer, Edward W.; Chisnall, Tom; Tano-Debrah, Kwaku; Card, Roderick M.; Duodu, Samuel; Kunadu, Angela Parry-Hanson (Frontiers in Microbiology, 2023)
Salmonella enterica are important foodborne bacterial pathogens globally associated with poultry. Exposure to Salmonella-contaminated eggs and egg-related products is a major risk for human salmonellosis. Presently, there is a huge data gap regarding the prevalence and circulating serovars of Salmonella in chicken eggs sold in Ghana. In this study, from 2,304 eggs (pools of six per sample unit) collected from informal markets in Accra, Kumasi and Tamale, representing the three ecological belts across Ghana, were tested for Salmonella. Antimicrobial susceptibility testing and Whole Genome Sequencing (WGS) of the isolates were performed using standard microdilution protocols and the Illumina NextSeq platform, respectively. The total prevalence of Salmonella was 3.4 5.5% with a higher rate of contamination in eggshell (4.9%) over egg content (1.8%). The serovars identified were S. Ajiobo (n=1), S. Chester (n=6), S. Hader (n=7), S. Enteritidis (n=2); and S. I 4:b:-(n=8). WGS analysis revealed varied sequence types (STs) that were serovar specific. The S. I 4:b:-isolates had a novel ST (ST8938), suggesting a local origin. The two S.Enteritidis isolates belonged to ST11 and were identified with an invasive lineage of a global epidemic clade. All isolates were susceptible to ampicillin, azithromycin, cefotaxime, ceftazidime, gentamicin, meropenem, and tigecycline. The phenotypic resistance profiles to seven antimicrobials: chloramphenicol (13%), ciprofloxacin (94%), and nalidixic acid (94%), colistin (13%), trimethoprim (50%) sulfamethoxazole (50%) and tetracycline (50%) corresponded with the presence of antimicrobial resistance (AMR) determinants including quinolones (gyrA (D87N), qnrB81), aminoglycosides (aadA1), (aph(3'')-Ib aph(6)-Id), tetracyclines (tet(A)), phenicols (catA1), trimethoprim (dfrA14 and dfrA1). The S. Enteritidis and S. Chester isolates were multidrug resistant (MDR). Several virulence factors were identified, notably cytolethal distending toxin (cdtB gene), rck, pef and spv that may promote host invasion and disease progression in humans. The findings from this study indicate the presence of multidrug resistant and virulent strains of Salmonella serovars in Ghanaian chicken eggs, with the potential to cause human infections. This is a critical baseline information that could be used for Salmonella risk assessment in the egg food chain to mitigate potential future outbreaks.